LEXICAL AND GRAMMATICAL UNITS IN INTERCULTURAL-BASED ENGLISH MATERIALS FOR ELEMENTARY SCHOOL - Fardini Sabilah (Informascope, 2018)
This current study focused on the development of intercultural-based instructional activities for elementary school students specifically in English subject. Lingual forms manifested in lexical and grammatical units were perceived to be able to capsulate various components of English subject in elementary school. The formulation of intercultural-based lingual forms is pivotal particularly as the basis in developing intercultural instruction so as to equip students with the skills to interact and communicate in English actively and efficiently. Intercultural instructional activities in elementary school is to be departed from students' characteristics, learning needs, proficiency levels, and learning styles. The designed instructional activities were expected to initiate students' English knowledge contextually; it is the necessary background to comprehend the foreign language based on social and cultural contexts of its native speakers (Gunarwan, 2007: 71). Descriptive qualitative design was employed. The variables were English instructional materials for Grade IV, V, and VI. The subjects were 2 English teachers. By means of observation and interview, this study has collected 55 data in the forms of lexical and grammatical units in intercultural-based English instructional activities. The lexical units included cultures, social or foreign values of English, some aspects not existing in Indonesian cultures or shared aspects existing in both cultures but of different lexical items translated from English. The grammatical units belonging to intercultural-based instructional activities were markers on different sentence constructions between English and Bahasa.